Insights and therapeutic advances in pancreatic cancer: the role of electron microscopy in decoding the tumor microenvironment - Dai, Hong; Chen, Xingxuan; Yang, Jiawen; Loiola, Rodrigo Azevedo; Lu, Aiping; Cheung, Kenneth C. P. (Frontiers in Cell and Developmental Biology, 2024)
Pancreatic cancer is one of the most lethal cancers, with a 5-year overall survival rate of less than 10%. Despite the development of novel therapies in recent decades, current chemotherapeutic strategies offer limited clinical benefits due to the high heterogeneity and desmoplastic tumor microenvironment (TME) of pancreatic cancer as well as inefficient drug penetration. Antibody- and nucleic acid-based targeting therapies have emerged as strong contenders in pancreatic cancer drug discovery. Numerous studies have shown that these strategies can significantly enhance drug accumulation in tumors while reducing systemic toxicity. Additionally, electron microscopy (EM) has been a critical tool for high-resolution analysis of the TME, providing insights into the ultrastructural changes associated with pancreatic cancer progression and treatment responses. This review traces the current and technological advances in EM, particularly the development of ultramicrotomy and improvements in sample preparation that have facilitated the detailed visualization of cellular and extracellular components of the TME. This review highlights the contribution of EM in assessing the efficacy of therapeutic agents, from revealing apoptotic changes to characterizing the effects of novel compounds like ionophore antibiotic gramicidin A on cellular ultrastructures. Moreover, the review delves into the potential of EM in studying the interactions between the tumor microbiome and cancer cell migration, as well as in aiding the development of targeted therapies like antibody-drug conjugates (ADCs) and aptamer-drug conjugates (ApDCs).